Integrating Epidemiological Modelsand Hospital Resource Management – A Demonstration of the Agent-Based Simulation Tool HosNetSim - Henke, Sebastian; Ponge, Johannes; Hellingrath, Bernd (Proceedings of the International ISCRAM Conference, 2025)
This paper presents the design and implementation of a unidirectional data interface connecting epidemiological forecasting models with hospital resource management tools, developed within the PROGNOSIS project to enhance hospital preparedness for pandemics and epidemics. We demonstrate the practical application of this interface through HosNetSim, a novel agent-based simulation tool specifically designed to support hospital and hospital group administrators, as well as public health authorities in hospital supply chain decision-making. The interface provides standardized, geographically specific, and daily updated forecasts of hospital burden across multiple respiratory diseases and care levels, enabling what-if scenario analysis. HosNetSim utilizes these forecasts to evaluate and visualize critical supply chain decisions, including inventory management policies, inventory pooling, and transshipments. By simulating realistic operational scenarios, HosNetSim illustrates the trade-offs between service levels and associated costs from the perspectives of individual hospitals, hospital groups, and regional networks.